To what extent have national learning objectives in undergraduate medical education been achieved? A cross-sectional study of primary care residents - Dehnen, Dorothea; Flägel, Kristina; Wild, Dorothea; Steinhäuser, Jost (GMS Journal for Medical Education)
Aim: 2021 saw the publication of the new version (2.0) of the “National Competency-based Catalogue of Learning Objectives (NKLM) in Undergraduate Medicine”, which in future will be closely linked to the German medical licensing regulations (ÄApprO). Included in the updated catalogue are specifically defined competencies concerning practical clinical skills. We aimed to determine how residents perceive their competency level to perform selected practical clinical skills in the NKLM 2.0. Method: In June 2022, all 593 medical residents registered at the competence centers for postgraduate training in primary care in North Rhine, Westphalia-Lippe and Schleswig-Holstein were invited to participate in an online survey. The participants were asked to retrospectively self-assess (1) their proficiency level (5-point Likert scale) at the beginning of their postgraduate training in regard to 36 practical clinical skills from the NKLM 2.0 and (2) where they had gained proficiency in those skills. Of the 164 participating residents, the main focus was on those who had been licensed for less than five years. Results: The responses of 47 residents were analyzed. For 29 skills, at least 20% of the participants stated that these had not been proficiently mastered at the start of postgraduate training; e.g., examining the spine of an adult (19.6%) or the skin (37.0%). For 14 skills – such as examining female and male genitalia and those of newborns and infants – more than 50% of the participants indicated that they had not been able to perform these skills. Conclusion: The results provide initial evidence that discrepancies may exist between the level of desired competency by the end of undergraduate medical education, as specified by the NKLM, and the level of proficiency actually achieved in terms of practical clinical skills. More teaching and feedback methods may need to be established to impart these skills during undergraduate medical education and to integrate these skills into complex clinical contexts.